# Sin(3x)cos(x)=cos(3x)sin(x)

## Simple and best practice solution for Sin(3x)cos(x)=cos(3x)sin(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Sin(3x)cos(x)=cos(3x)sin(x) equation:

Simplifying
Sin(3x) * cos(x) = cos(3x) * sin(x)
Remove parenthesis around (3x)
inS * 3x * cos(x) = cos(3x) * sin(x)
Reorder the terms for easier multiplication:
3inS * x * cos * x = cos(3x) * sin(x)
Multiply inS * x
3inxS * cos * x = cos(3x) * sin(x)
Multiply inxS * cos
3cinosxS * x = cos(3x) * sin(x)
Multiply cinosxS * x
3cinosx2S = cos(3x) * sin(x)
Remove parenthesis around (3x)
3cinosx2S = cos * 3x * sin(x)
Reorder the terms for easier multiplication:
3cinosx2S = 3cos * x * ins * x
Multiply cos * x
3cinosx2S = 3cosx * ins * x
Multiply cosx * ins
3cinosx2S = 3cinos2x * x
Multiply cinos2x * x
3cinosx2S = 3cinos2x2
Solving
3cinosx2S = 3cinos2x2
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3cinos2x2' to each side of the equation.
3cinosx2S + -3cinos2x2 = 3cinos2x2 + -3cinos2x2
Combine like terms: 3cinos2x2 + -3cinos2x2 = 0
3cinosx2S + -3cinos2x2 = 0
Factor out the Greatest Common Factor (GCF), '3cinosx2'.
3cinosx2(S + -1s) = 0
Ignore the factor 3.
Subproblem 1Set the factor 'cinosx2' equal to zero and attempt to solve:
Simplifying
cinosx2 = 0
Solving
cinosx2 = 0
Move all terms containing c to the left, all other terms to the right.
Simplifying
cinosx2 = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(S + -1s)' equal to zero and attempt to solve:
Simplifying
S + -1s = 0
Solving
S + -1s = 0
Move all terms containing c to the left, all other terms to the right.
Add '-1S' to each side of the equation.
S + -1S + -1s = 0 + -1S
Combine like terms: S + -1S = 0
0 + -1s = 0 + -1S
-1s = 0 + -1S
Remove the zero:
-1s = -1S
Add 's' to each side of the equation.
-1s + s = -1S + s
Combine like terms: -1s + s = 0
0 = -1S + s
Simplifying
0 = -1S + s
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`